2015
DOI: 10.17051/io.2015.12578
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Teknolojik Pedagojik Alan Bilgilerinin İncelenmesi

Abstract: ABSTRACT. The purpose of this study is to investigate the relationship between demographic and technology related variables with Technological Pedagogical Content Knowledge (TPACK) of primary school teachers. The participants were 411 primary school teachers in the city of Edirne who volunteered to answer the online data collection instrument. The first part of the instrument consisted of items on demographics and technology use. The second part was the TPACK instrument developed by Schmidt, et.al (2009) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
2
5
0
4
Order By: Relevance
“…The teachers who have 30-39 years experience had higher score than the teachers who have 10-19 years experience in pedagogical content knowledge dimension. The study of Karadeniz and Vatanartıran (2015) supports this result. Teachers' experience influences their selection of teaching strategies, methods and techniques, and assessment as well as being effective that this may explain this result.…”
Section: Discussionsupporting
confidence: 78%
“…The teachers who have 30-39 years experience had higher score than the teachers who have 10-19 years experience in pedagogical content knowledge dimension. The study of Karadeniz and Vatanartıran (2015) supports this result. Teachers' experience influences their selection of teaching strategies, methods and techniques, and assessment as well as being effective that this may explain this result.…”
Section: Discussionsupporting
confidence: 78%
“…Roussos (2007) stated in his study that gender is not a significant factor in determining selfconfidence levels. In the literature, there are similar findings (Karadeniz and Vatanartıran, 2015;Şad and Nalçacı, 2015). However, there are studies that have shown a significant relationship between gender and self-confidence scores (Akgül et al, 2015;Gönen and Kocakaya, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…Ortaokullarda çalışan branş öğretmenlerinin çoğu teknoloji kullanım düzeyi olarak iyi olduğunu söylemekle birlikte teknolojiyi derslerine entegre edebilme düzeylerinin biraz daha az olduğunu söylemektedirler. Karadeniz ve Vatanartıran (2015) araştırmalarında öğretmenlerin teknolojiyi kullanabilmeleri için teknolojiye karşı olumlu tutum geliştirmeleri gerektiğini ifade etmektedirler. Balanskat, Blamire ve Kefala (2006) yaptıkları araştırmada, öğretmenlerin bilişim teknolojilerini kullanma konusunda yeterli beceriye sahip olmadıkları ve teknolojiyi derslerine entegre etme konusunda isteksiz olduklarını vurgulamaktadırlar.…”
Section: Sonuç Ve Tartişmaunclassified